Occupational Health and Safety (OHS) Risk Control Analysis at a Tofu Factory Using the Job Safety Analysis (JSA) Method - Mikael Julfian Mule; Mardhiah Gani; Sanny Hahury; Mirga Maulana Ramadhani; Siti Nur Kayatun (PT. SAFARI AMALIA, 2026)
Tahu Bintang Salma Factory is a company engaged in the tofu manufacturing industry. The factory continuously faces occupational accident issues in the form of blistered skin, itchy skin, eye irritation, and sprained feet, all of which disrupt the production process. This study identifies work accidents occurring at Tahu Bintang Salma Factory and proposes occupational health and safety (OHS) control methods to address these problems. Data were collected and processed using the Job Safety Analysis (JSA) method. Results revealed eleven potential hazards: spinal pain, bruised hands, bruised feet, sprained feet, tailbone injury, blistered skin, eye irritation, reddened skin, skin irritation (itching), bruised fingers, and hand lacerations. These risks were categorized into four levels: six low-risk, three moderate-risk, and two high-risk incidents. Control measures including administrative controls, personal protective equipment (PPE), and substitution were proposed to mitigate or reduce the potential for workplace accidents.